MEO SAR: System Concepts and Analysis - Matar, Jalal; Rodriguez-Cassola, Marc; Krieger, Gerhard; Lopez-Dekker, Paco; Moreira, Alberto (IEEE Transactions on Geoscience and Remote Sensing, 2020)
Existing microwave remote sensing instruments used for Earth observation face a clear tradeoff between spatial resolution and revisit times at global scales. The typical imaging capabilities of current systems range from daily observations at kilometer-scale resolutions provided by scatterometers to meter-scale resolutions at lower temporal rates (more than ten days) typical of synthetic aperture radars (SARs). A natural way to fill the gap between these two extremes is to use medium-Earth-orbit SAR (MEO-SAR) systems. MEO satellites are deployed at altitudes above the region of low Earth orbits (LEOs), ending at around 2000 km and below the geosynchronous orbits (GEOs) near 35 786 km. MEO SAR shows a clear potential to provide advantages in terms of spatial coverage, downlink visibility, and global temporal revisit times, e.g., providing moderate resolution images (some tens of meters) at daily rates. This article discusses the design tradeoffs of MEO SAR, including sensitivity and orbit selection. The use of these higher orbits opens the door to global coverage in one- to two-day revisit or continental/oceanic coverage with multidaily observations, making MEO SAR very attractive for future scientific missions with specific interferometric and polarimetric capabilities.
Created from Fastlane, Scopus look-up
Keywords: Coverage; medium-Earth-orbit (MEO) synthetic aperture radar (SAR); orbits; SAR; space radiation; system performance